Scambio di embrioni: errore medico e scissione delle figure genitoriali (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
A famous, recent news item represents the occasion for this paper, that reflects about the problem of embryos’ mix?up. Starting from the judgement that the Tribunal of Rome gave in that case, the author analyses the legal and ethical aspects of this situation, hoping that in the future both judges and the law?maker can give prevalence to the best interest of the minor.
Keywords: embryosâ€™ mixâ€up; gametesâ€™ donation; best interest of the child; medically assisted reproduction; parental roles.